Biogas Production from Livestock Manure via Anaerobic Digestion and Co-Digestion: A Comprehensive Review of Processes, Microbial Roles, Technological Perspectives, and Opportunities - Prasiefa, Mizanurafi' Ghifarhadi; Ali, Mohammad Nazarudin (University of Jember, 2026)
Anaerobic co-digestion (AcoD) of livestock manure is widely recognized for enhancing biogas production; however, its performance is governed by complex interactions between substrate characteristics, microbial consortia, and reactor configurations, which are often addressed separately in existing reviews. This study provides an integrated assessment of manure-based AcoD by linking microbial dynamics, feedstock variability, and technological design to identify key factors controlling methane (CH4) yield and process stability. Mono-digestion is frequently limited by imbalanced C/N ratios and ammonia (NH3) inhibition, whereas co-digestion with plant-based substrates improves nutrient balance and promotes microbial synergy. The AD process involves four stages—hydrolysis, acidogenesis, acetogenesis, and methanogenesis–driven by bacteria (Firmicutes, Bacteroidetes) and methanogenic archaea (Methanoculleus, Methanosarcina), whose activity is strongly influenced by operating conditions. Various livestock manures, including cow/cattle, bovine, sheep, goat, llama, pig/swine, buffalo, horse, donkey, deer, camel, duck, rabbit, chicken, poultry, fish, shrimp, as well as human waste, have been tested under different co-digestion conditions with plant-derived feedstocks. Across various manure types and co-digestion systems, CH4 content ranges from 46–78%, with yields up to 8905 ± 70.7 mL CH4/g-VS under optimized conditions. This review highlights that optimizing parameters such as the C/N ratio (25–30:1), temperature (35–55 ℃), and organic loading rate (OLR), along with appropriate reactor selection and microbial management, is critical to maximizing performance. Despite these advances, challenges related to NH3 inhibition, feedstock variability, and scale-up remain. Future work should focus on integrated system design, real-time monitoring, and cost-effective process optimization to support the large-scale implementation of manure-based AcoD.